Pengenalan Panel Surya sebagai Salah Satu Sumber Energi Terbarukan untuk Pembelajaran di SMA Negeri 1 Takalar - Fitriyanti Mayasari; Faizal Arya Samman; Zaenab Muslimin; Tajuddin Waris; Dewiani Dewiani; A. Ejah Umraeni Salam; Indar Chaerah Gunadin; Intan Sari Areni; Yusri Syam Akil; Ida Rachmaniar Sahali; Azran Budi Arief (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
The rapid development of technology, the trend that leads to the green earth movement and the encouragement of the use of new and renewable energy (EBT) by the government, have become the basis for the importance of introducing small-scale EBT generation equipment to the society, especially to students. Solar energy is one the source of renewable energy that has considerable potential and is spread evenly in Indonesia. Solar Panels as the main component of Solar Power Plants (PLTS) have qualified and advanced technology. The application has been widely used by both industry and urban communities. This activity was carried out by the Department of Electrical Engineering Unhas to introduce solar panels as a source of EBT to high school students of SMA Negeri 1 Takalar, Pattalassang Subdistrict, Takalar Regency through outreach activities. By this activity, the students will have an understanding of the basic principles, components of small-scale PV and its latest technology. This activity also produces a small-scale PLTS module which will be given to SMA Negeri 1 Takalar, in order for continuous learning can be carried out. To measure the level of success of the activity, pre- and post-activity assessments were conducted in the form of a questionnaire to students with parameters related to the basic understanding of PLTS. The results of the quantitative analysis of the questionnaire showed an increase in the level of student understanding reaching 44-56% after the service activities were carried out. Therefore, this activity gives the expected results.